The Influence of an Exogenous Microbial Enzyme Supplement on Feed Consumption, Body Growth and Follicular Development of Pre-Lay Pullets on Maize-Soy Diets - Chauynarong, N.; Iji, P.A.; Isariyodom, S.; Mikkelsen, L. (International Journal of Poultry Science, 2008)
An experiment was conducted to examine the benefits of supplementing maize-soy diets with a composite microbial enzyme, Allzyme SSF, for laying hens at the pullet stage. Seven hundred and twenty 12-week old Isa Brown pullets were used in the different level of protein content diets. Feed intake from 12 to 16 weeks of age was unaffected by the enzyme supplement, except at the lowest protein content (P